1989
DOI: 10.1212/wnl.39.5.736
|View full text |Cite
|
Sign up to set email alerts
|

Brachial plexus injury following liver transplantation

Abstract: We examined 7 adults with brachial plexus injury following liver transplantation; they were among 120 transplants performed over a 10-month period (incidence, 5.8%). The lesion was right-sided in 5 patients, left-sided in 1, and bilateral in 1. The affected side correlated with the axillary veno-venous shunt in 3 lesions only. All noted weakness and sensory loss shortly after recovery from general anesthesia. The EMG examination indicated axonal lesions, and recovery was protracted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Five recently underwent liver transplantation and 1 had a thoracotomy, and it was thought that the plexopathies were due either to stretch injuries or trauma from axillary vein cannulations. 23 Postoperative ParsonageTurner syndromes 31 could not be excluded. Another was in a motor vehicle accident and had multiple upper extremity fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Five recently underwent liver transplantation and 1 had a thoracotomy, and it was thought that the plexopathies were due either to stretch injuries or trauma from axillary vein cannulations. 23 Postoperative ParsonageTurner syndromes 31 could not be excluded. Another was in a motor vehicle accident and had multiple upper extremity fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have indicated a relatively high incidence of neurological complications during liver transplantations; brachial plexus injury was seen in 5.8% of cases (7 of 120 patients) [6], and neuromuscular complications in 3.8% (24 of 627 patients including 6 cases of brachial plexus neuropathies) [7], in two separate reports of patients undergoing liver transplantation. It was suggested that these neuropathies were probably related to prolonged anesthesia, invasive central venous monitoring catheters, and surgical procedures such as venovenous bypass.…”
Section: Discussionmentioning
confidence: 96%
“…Surgical procedure of organ transplantation may result in peripheral nerve palsies due to operative positioning, coldinduced injury, or nerve traction injury [16,17]. Prolonged surgery and operative positioning may precipitate postoperative mononeuropathies, including peroneal, femoral, and ulnar palsies [18][19][20][21].…”
Section: Neuromuscular Complications Related To Transplantation Surgerymentioning
confidence: 99%
“…Phrenic neuropathy and recurrent laryngeal nerve injury are more frequent with thoracic organ transplantation and rarely may occur after liver transplantation as well [17,20]. Brachial plexopathy may occur after thoracic or liver transplantation [16,20]. Lumbosacral plexopathy and femoral neuropathy have been reported after kidney transplantation [21,22].…”
Section: Neuromuscular Complications Related To Transplantation Surgerymentioning
confidence: 99%
See 1 more Smart Citation